Rethinking legal taxonomies for the gig economy - Adams, A; Freedman, J; Prassl, J (Oxford University Press, 2018)
Both tax law and employment law incentivize engagers of labour to structure their workforce as a crowd of self-employed micro-entrepreneurs. Recent technological change and the rise of the gig economy have made it easier for agents to respond to these incentives, contributing to an increase in self-employment. In this article, we review the evidence on the rise of the gig economy in the UK and lay out a set of key principles to guide the reform of tax and employment law to better enable policy to meet its underlying objectives.